2004
DOI: 10.1890/02-5409
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Indicator Groups of Tropical Land‐use Systems: Comparing Plants, Birds, and Insects

Abstract: Tropical landscapes are dominated by land‐use systems, but their contribution to the conservation of biodiversity is largely unknown. Since changes in biodiversity in response to human impact are known to differ widely among taxonomic groups and guilds, there is a need for multidisciplinary collaboration of plant, vertebrate, and invertebrate experts. We used inventories of trees, understory plants, birds (subdivided into endemics, insectivores, frugivores/nectar feeders), butterflies (endemics, fruit feeders)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
275
3
19

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 427 publications
(317 citation statements)
references
References 81 publications
(84 reference statements)
20
275
3
19
Order By: Relevance
“…Only forest-based trees, herbs, and canopy ants tended to decline with shade cover reduction, whereas species richness of other groups, both forestand non-forest-based species, remained constant. Other studies have reported a significant reduction in biodiversity along land-use intensification gradients in the tropics (5,6,19,20,25). This discrepancy is likely due to different extents in the analyzed land use gradients, with most studies also including agricultural systems completely devoid of trees.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Only forest-based trees, herbs, and canopy ants tended to decline with shade cover reduction, whereas species richness of other groups, both forestand non-forest-based species, remained constant. Other studies have reported a significant reduction in biodiversity along land-use intensification gradients in the tropics (5,6,19,20,25). This discrepancy is likely due to different extents in the analyzed land use gradients, with most studies also including agricultural systems completely devoid of trees.…”
Section: Discussionmentioning
confidence: 96%
“…The transition from forest to cacao agroforestry resulted in a loss of Ϸ60% of the forest-based species with plant species being more strongly affected than mobile insect taxa. It seems reasonable to assume that rare, specialized, and endangered species are represented disproportionately high in this fraction (6), underlining the limitations of agroforestry for conservation of forest species (16). Unfortunately, detailed distributional and ecological data are lacking on most species encountered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candidate indicators such as landscape metrics, remotely-sensed variables, multi-species indices and formulated measures of ecosystem complexity or genetic diversity have found wide application but are of limited practicality in forests (UNEP-CBD 1996; Kapos et al 2001;Delbaere 2002; European Academies' Science Advisory Council (ESAC) 2004; Gregory et al 2005;Duraiappah and Naeem 2005). Thus forest biodiversity surveys still maintain a taxonomic focus even though the costs of obtaining sufficient sampling can be high and the utility of any one species, or another single taxon, as a predictor of others remains uncertain (Lawton et al 1998;Watt et al 1998;Dufrêne and Legendre 1997;UNEP/CBD 2003;Gregory et al 2005, but see also Schulze et al 2004). Further, at large spatial scales where within-region diversity is large, higher level taxa (up to family level) must often be used (Villaseñor et al 2005), but even this is only justifiable where extensive species data are already available (Sarkar et al 2005).…”
Section: Introductionmentioning
confidence: 99%